Resource Development of Entrepreneurs of Small and Medium Enterprise (SME) of Wooden Batik Center in Putat Village and Sendangsari Village - Aryan Torrido; Ravik Karsidi (Nusantara Science and Technology Proceedings, 2020)
Covid 19 Pandemic that hit many countries has led to changes in consumer behav-ior as in shifting target products as well as consumption patterns with wider digital use. This situation leads to the use of information technology by entrepreneurs in small and medium-scale businesses but the encouragement to make good use of it goes slow. It is caused by a lack of entrepreneurial mindset development owned by entrepreneurs. Therefore, this research aims to find out how far entrepreneurial mindset development is implemented in the development target community, by conducting a study on capacity building activity of workshop owners’ resource in the wooden batik center of Putat Village and Sendangsari Village. The qualitative research method was used with a multiple case approach. The research result shows that in the last six years, there has been no more entrepreneurial mindset training held by the government and private institutions. The psychological ap-proach that is still done is to encourage workshop owners of wooden batik cen-ters. Empowerment activities are necessary to be considered so that the activities are not only aimed at the target community but also the actors who need to be em-powered first. Therefore, disorientation will not happen and the objectives of de-velopment activities can be implemented more efficiently and effectively.